Exact solutions for MHD natural convection flow near an oscillating plate emerged in a porous medium - Mohammed, Abdulhameed (Penerbit UTM Press, 2012)
Analytical investigation was conducted on the transient natural convection flow past an oscillating infinite vertical plate in present of magnetic field and radiative heat transfer. The classical solution of this problem for impulsively moving plate is given by Seth in [2] and is found to be a special case of the solution to be presented. The governing model equations are solved analytically with the help of Laplace transform technique. The results are expressed in terms of the velocity and temperature profiles as well as the skin-friction and Nusselt number.